GOALS AND OBJECTIVES OF TEACHERS IN A CLASSROOM (Ustozlar uchun, 2025)
This article explores the fundamental goals and objectives of teachers in a classroom setting. It emphasizes the importance of teachers’ roles in promoting not only academic success but also the social, emotional, and moral development of students. The paper discusses how clear goals help to maintain focus, motivate learners, and create a productive learning environment. It also considers the connection between teachers’ objectives and modern educational standards, highlighting how goal-oriented instruction contributes to the holistic development of students.